BEHAVIOR OF SILVER AND GOLD NANOPARTICLES IN SIMULATED BIOLOGICAL FLUIDS: NEEDS AND CHALLENGES - DINCA, Zamfira; MOCAN, Teodora; SENILA, Lacrimioara; CADAR, Oana (Studia Universitatis Babeș-Bolyai Chemia, 2021)
Nanotechnology is an attractive and challenging science focused on the materials at nanoscale level and their employment in a wide variety of applications. Its applications in (nano)medicine are constrained due to the main concerns in understanding and predicting the behavior of nanoparticles (NPs) in complex biological fluids. The properties of NPs can be strongly influenced by the surrounding conditions, such as pH and composition, in terms of aggregation status, chemical reactivity and surface chemistry. In this regard, this review intents to provide some insight into the performance of complex biological fluids associated with nanomaterials. In particular, the behavior of AgNPs and AuNPs in simulated biological fluids that must be addressed to develop an appropriate system for medical applications, from a chemical perspective, mostly related to the physico-chemical characteristics of NPs and simulated biological fluids and their possible interactions (mechanisms) was considered. Furthermore, the fate of AgNPs and AuNPs during the gastrointestinal transit from an in vivo experimental perspective, as well as their potential impact on gut microbiota was also systematized.